Implementasi Akad Rahn Di Pegadaian Syariah Untuk Meningkatkan Kesadaran Tentang Keuangan Syariah - fitriani rahmadani as'ha; Masyhuri; ruqyah_26 kiya (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study examines the implementation of rahn contract in Islamic pawnshops in Indonesia, highlighting the challenge of low public awareness of Islamic financial principles. Despite the rapid growth of Islamic finance, many individuals utilize Islamic pawn services primarily for practical reasons rather than understanding Islamic financial principles. This study uses a qualitative descriptive method, utilizing purposive sampling to gather insights from relevant informants, including managers, staff, and customers of Islamic pawnshops. The study findings reveal that Islamic pawnshops comply with Islamic law by avoiding usury and ensuring transparency in transactions through ujrah fees. However, public understanding is still limited, requiring more comprehensive and interactive education strategies, such as seminars and workshops, to improve financial literacy in the community. This study aims to contribute to strengthening Islamic financial literacy and developing more inclusive Islamic financial services. Keywords: Islamic finance, rahn contract, financial literacy, pawnshops, Indonesia.